Pengembangan Kuisioner Udayana untuk Penilaian Kepuasan Pasien terhadap Pelayanan Kefarmasian oleh Apoteker di Pusat Kesehatan Masyarakat - Luh Putu Febryana Larasanty; Made Krisna Adi Jaya; Ketut Widyani Astuti; I Wayan Martadi Santika (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The implementation of pharmaceutical care by pharmacists at the community health center has been regulated in the Minister of Health Regulation No. 74 of 2016. Based on that regulation, assessment of pharmaceutical care services is needed to ensure the quality of services provided by pharmacists. This study aims to develop an Udayana questionnaire that can be used to evaluate the quality of pharmaceutical care provided by pharmacists at community health centers. This research is quantitative (survey implementation) carried out in 2 phases. The first phase is the design of the Udayana questionnaire. The second phase is to verify the validity and reliability of the questionnaire. The questionnaire validity test was carried out in three stages, namely the logical validity test, content validity, and construct validity. The questionnaire statement develop based on Minister of Health Regulation No. 74 of 2016 obtained 31 statements which are divided into 5 dimensions of service quality. The logical validity test resulted in 30 statements that were declared valid by experts. Content validity test is done by calculating the value of the content validity ratio (CVR) and the value of the content validity index (CVI). The CVR and CVI results showed that 7 statements were eliminated because they were not valid (CVR value <0.99 and CVI <70%). Construct validity test and questionnaire reliability were tested on 384 respondents who had met the inclusion criteria. The construct validity test resulted 23 valid statement (r = 0.148). Results of the reliability test based on Cronbach's Alpha value is greater than 0.6, indicating that all the valid statement items in the Udayana questionnaire are reliable. Based on the results of validity and reliability tests, 23 statements of Udayana's questionnaire are stated valid and reliable and can be used to evaluate the quality of pharmaceutical care at the community health center.